The effects of syntactic vs. semantic feature analysis of words on Iranian EFL learners' reading comprehension - Sepasdar, Mansoure; Rostampour, Mohammad (Frontiers in Education, 2022)
Introduction The development of learners' semantic and syntactic knowledge of words and vocabulary plays an essential role in reading comprehension. This study attempted to investigate and compare the impact of instructing syntactic and semantic analyses of word features on Iranian EFL learners' reading comprehension. Methods Three groups were selected: one was the control group and two were used as experimental groups. Students in all groups took part in a reading pretest. Two experimental groups received specific treatments, while the control group followed a traditional syllabus. All groups took part in a reading comprehension posttest at the end of the syllabus. Results and discussion The results revealed that the syntactic analysis group outperformed the semantic analysis and control groups in the posttest. In addition, the participants in the semantic analysis group outperformed the students in the control group in the posttest. The results of this study could help teachers, learners, and textbook writers to improve reading skills in teaching, learning, and material development.